Las Remiendavirgos en el Siglo de Oro - Kriz, Kurt (Avisos de Viena, 2021)
The practice of hymen reconstruction, known as "remendar virgos" or virgin-mending, may seem like a relic of the past, but it persists today. Drawing from thirty years of experience as a gynecologist in Vienna, the author explores the historical and contemporary significance of hymen reconstruction, particularly in cultures where virginity holds significant social value, such as in the Middle East. Examining literary works from the early Modern Spanish period, the article highlights references to "remiendavirgos" or virgin-menders, who clandestinely restored women's virginity using various methods, including hymen reconstruction and inducing bleeding. Despite the absence of detailed medical explanations in Golden Age medical treatises, literary texts like Fernando de Rojas' "La Celestina" provide insights into the tools and techniques employed by these clandestine practitioners.